Аналіз переваг та недоліків денормализації баз даних - Колокольчева, С. А. (ХНУРЕ, 2023)
The negative effects of denormalizing databases are covered in this thesis. Denormalization is the process of adding redundancy consciously to a database to boost performance. This method, however, may result in inconsistent data, duplicate data, and more maintenance work